ChemInform Abstract: Carbohydrates as Ligands for Enantioselective Synthesis. Issue 49 (9th December 2014) - Bauer, Tomasz; Majdecki, Maciej
Abstract Review: [applications of carbohydrate‐derived ligands in enantioselective transition meal catalysis since 2008]